Similar Effects of General and Spinal Anaesthesia on Perioperative Stress Response in Patients Undergoing Haemorrhoidectomy (Mediators of Inflammation)
Surgery induces release of neuroendocrine hormones (cortisol), cytokines (interleukin-6: IL-6, tumour necrosis factor- α : TNF- α ), acute phase proteins (C-reactive protein: CRP, leptin). We studied the effects of general and spinal anaesthesia on stress response to haemorrhoidectomy. Patients were assigned to general and spinal anaesthesia groups ( n = 7 ). Blood samples were drawn before induction and 24 hours after surgery. Perioperative levels of IL-6, TNF- α , CRP, cortisol, and leptin were comparable among the groups. Twenty four hours after surgery, TNF- α and cortisol did not change; IL-6 and CRP increased significantly in all patients. Significant increase in leptin levels was found in patients undergoing spinal anaesthesia. Except for the increase in leptin levels, there was no significant difference related to the effects of general and spinal anaesthesia.